Development of Carcinoembryonic Antigen Rapid Detection System Based on Platinum Microelectrode - Zhai, Jiali; Ji, Piyou; Xin, Yu; Liu, Yifan; Qu, Qianwen; Han, Wentong; Zhao, Guangtao (Frontiers in Chemistry, 2022)
Rapid and highly sensitive detection of carcinoembryonic antigen (CEA) in blood could effectively improve the diagnostic sensitivity of colorectal cancer. In this work, a platinum microelectrode (PtμE) modified with gold nanoparticles was developed as microsensor for the detection of CEA. As the recognition element, CEA aptamer modified with sulfydryl could be conjugated onto the surface of the PtμEs/Au. The quantitative analysis of the concentration of CEA [CEA] by the prepared PtμEs/Au aptasensor was carried out through square wave voltammetry. Under the optimized conditions, the PtμEs/Au aptasensor exhibits a linear response toward [CEA] in the range of 1.0 × 10-11 - 1.0 × 10-7 g/mL (S=5.5 nA/dec, R2=0.999) and the detection limit is 7.7 × 10-12 g/mL. The PtμEs/Au aptasensor also has good selectivity against other types of proteins existing in blood. The availability of the developed assay toward [CEA] in blood samples was investigated, and the results agree well with those obtained through electrochemiluminescence provided by the hospital, and the volume of the blood sample for detection is only 20 μL. Herein, the proposed detection system could be used for the quantitative analysis of CEA in blood with the advantages of high sensitivity, short time, and low cost. Moreover, the PtμEs/Au aptasensor has a potential application in clinical diagnose.